Going home to glory : a memoir of life with Dwight D. Eisenhower, 1961-1969 - Eisenhower, David, 1948-; Eisenhower, Julie Nixon (New York : Simon & Schuster, 2010)
David Eisenhower delivers a warm, personal recollection of the retirement years of his grandfather, Dwight D. Eisenhower, in Gettysburg, Pennsylvania, where they lived.
Includes bibliographical references (p. [299]-303) and index.
Keywords: Eisenhower, Dwight D. -- 1890-1969.; Eisenhower, Dwight D. -- 1890-1969 -- Family; Eisenhower, David, -- 1948-; Presidents -- United States -- Biography; Ex-presidents -- United States -- Biography